Effects of the walnut Plukenetia conophora shell in the diet on the growth performance and genotoxicity of the African catfish Clarias gariepinus - Simeon O. Ayoola; Loveth N. Omoile (Syiah Kuala University, 2019)
Aquaculture industry is facing challenges of the high cost of fish feed, and therefore it is very crucial to explore the alternative raw materials for feed formulation at the lowest cost. Therefore, the objective of the present study was to evaluate the effect of Plukenetia conophora shells on the growth, haematological and biochemical parameters, and its genotoxicity on African catfish Clarias gariepinus juveniles. Five experimental diets were formulated having three replicates at 0% (0WS), 25% (25WS), 50% (50WS), 75% (75WS) and 100% (100WS) inclusion of walnut shell respectively. The fishes were fed on experimental diet two time a day for 12 weeks. The results showed that the fish in tank 25WS had the best weight gain with the mean of 33.5±5.8 g and the least was recorded in tank 100WS. The specific growth rate was highest in-tank 75WS with the mean value of 0.46±0.05 g was recorded. The highest feed intake was found in fish fed with 25% inclusion of P. conophora. The fish fed with P. conophorashowed increased values of haemoglobin, (12.05±1.63g/dL), Red blood cell, (2.785±0.28µL) and White blood cell, (11.25±4.59µL) compared with control diet values of fish fed of Red blood cell, (1.81±1.54µL) and White blood cell, (5.15±6.57µL). There was a reduction in the haematological value of the fish fed with control feed having Haemoglobin, (10.75±8.13g/dL). The genotoxicity test that was carried out showed that the highest counts of micronucleus were in tank 75WS. The Duncan Multiple Range Test (DMRT) shows a significant difference (p0.05) in the growth performance of the fish. It is concluded that inclusion of 50% P. conophora shells in the feed of C. gariepinus gave no negative impact on the health status and growth performance of the fish. Keywords: Toxicity test, Growth indices, Plukenetia conophora, Clarias gariepinus